Workshop Report: AMR in Aquaculture - Result Sharing and Way Forward - Rheman, Shafiq; Hossain, Sabrina; Al Mahmud, Abdullah (WorldFish, 2024)
On November 16, 2024, WorldFish organized a one-day workshop titled “AMR in Aquaculture: Results Sharing and Way Forward” in Dhaka to present the findings and lessons learned from the research study. The workshop engaged diverse actors in addressing the antimicrobial resistance (AMR) challenges facing Bangladesh's aquaculture sector. A total of 59 participants from a diverse range of stakeholders attended the workshop, including representatives from government agencies, academics from various universities, development organizations, research institutes, veterinarians and other practitioners, and farmers. The participants brought a wide array of perspectives and expertise, contributing to enriching discussions and collaborative efforts to address the pressing issue of AMR in Bangladesh's aquaculture. The workshop was structured into four main sessions: open talk, result sharing, community voices, and group activity sessions.